Rationing in healthcare—a scoping review - Berezowski, Jakub; Czapla, Michał; Manulik, Stanisław; Ross, Catherine (Frontiers in Public Health, 2023)
Healthcare rationing has been the subject of numerous debates and concerns in the field of health economics in recent years. It is a concept which refers to the allocation of scarce healthcare resources and involves the use of different approaches to the delivery of health services and patient care. Regardless of the approach used, healthcare rationing fundamentally involves withholding potentially beneficial programs and/or treatments from certain people. As the demands placed on health services continue to rise and with that significant increases to the cost, healthcare rationing has become increasingly popular and is deemed necessary for the delivery of affordable, patient-care services. However, public discourse on this issue has largely been centered on ethical considerations with less focus on economic rationality. Establishing the economic rationality of healthcare rationing is essential in healthcare decision-making and consideration of its adoption by healthcare authorities and organizations. This scoping review of seven articles demonstrates that the economic rationality of healthcare rationing is the scarcity of healthcare resources amidst increased demand and costs. Therefore, supply, demand, and benefits are at the core of healthcare rationing practices and influence decisions on its suitability. Given the increased costs of care and resource scarcity, healthcare rationing is a suitable practice towards ensuring healthcare resources are allocated to people in a rational, equitable, and cost-effective manner. The rising costs and demands for care place significant pressure on healthcare authorities to identify suitable strategies for the allocation of healthcare resources. Healthcare rationing as a priority-setting strategy would support healthcare authorities identify mechanisms to allocate scarce resources in a cost-effective manner. When used in the context of a priority-setting approach, healthcare rationing helps healthcare organizations and practitioners to ensure that patient populations achieve maximum benefits at reasonable costs. It represents a fair allocation of healthcare resources to all populations, especially in low-income settings.